Optimal auctions with externalities and signaling - Jozsef Molnar; Gabor Virag (Hungarian Academy of Sciences, Institute of Economics, 2001)
This paper asks how to design a revenue-maximizing auction in the presence of post-auction market competition and asymmetric information. In this situation, bidders, depending on the auction mechanism, can signal their type through their bidding behavior which influences the outcome of the post-auction market game. Thus the auctioneer has to design a mechanism that not only specifies who wins the good but also describes the amount of information that can be revealed about the winer through signaling. This paper shows that to reveal all information about the winner can be optimal under some conditions.
Keywords: 330